Addressing UAV Communication Latency: A Simulation Approach with Networked Model Predictive Control in CoppeliaSim and Mininet-wifi - Barros, Mateus Rodrigues de; Soares, Igor Mayer; Marcondes, Cesar (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This paper investigates the effect of communication latency on UAVs controlled over wireless networks. We introduce a Networked Model Predictive Control (MPC) framework in MATLAB/Simulink to mitigate delay effects. A virtual environment combining CoppeliaSim, and Mininet-Wifi is used to emulate real-time UAV operations under varying latency. The UAV is connected to a Ground Control Station (GCS) through an emulated wireless network, and communication response times are measured. Results show that the Networked MPC significantly improves UAV flight stability, preventing degradation and control surface saturation observed in scenarios without delay compensation. This demonstrates the effectiveness of Networked MPC in ensuring safe UAV operations under dynamic wireless communication conditions.